Al sur de las palabras, de María José Sierra Calle, Granada, Editorial Alhulia, 2013. - Juan de Dios Villanueva Roa (Investigaciones Sobre Lectura)
Reseña de Al sur de las palabras, de María José Sierra Calle, Granada, Editorial Alhulia, 2013.